Integrating Active Learning within an AI-Supported Gamified Environment through Zep Quiz to Improve Arabic Language Achievement - Ahmad Sucipto Mulyo Utomo; Robiyah Nur; Damanhuri; Erni Zuliana (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2026)
This study investigates the integration of Active Learning into an AI-supported gamified environment through Zep Quiz to improve Arabic language achievement among seventh-grade students at MTs Negeri 1 Bandar Lampung. The study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, consisting of two cycles involving 32 students. Data were collected through classroom observations, learning achievement tests, and documentation. Quantitative data were analyzed using mean scores, classical mastery percentages, and N-Gain, while qualitative data were analyzed through observations of student engagement during the learning process. The findings reveal that the integration of Active Learning and Zep Quiz successfully enhanced both student engagement and Arabic language achievement. The average score increased from 52.38 in the pre-cycle stage to 78.13 in Cycle I and 87.50 in Cycle II. Similarly, classical mastery improved from 28.13% to 65.63% and eventually reached 90.63%, exceeding the predetermined success criterion of 85%. The N-Gain score of 0.74 indicates a high level of improvement. These findings suggest that AI-supported gamified learning environments can effectively support Active Learning and foster meaningful improvements in Arabic language learning outcomes.